FORMS AND MECHANISMS OF LAW DISPUTE RESOLUTION USING THE PRINCIPLE OF PANCASILA BASED ON LOCAL WISDOM - Muhammad Taufiq; Sarsiti .; Rindha Widyaningsih (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Dispute resolution in the society should be solve by the value of local wisdom. Substantially, the value of local wisdom in Banyumas have synergy with the principle of Pancasila as the source of all law source. This study uses qualitative descriptive study specifications. The test method is done by triangulation of data sources and data were analyzed using content analysis method by way of presenting data in the form of narrative text. The result is there are four types of local wisdom Banyumas which is a resource for the settlement of legal disputes that occur in society that is the tradition cablaka/ blakasutha/ thokmelong, egalitarian, rembugan traditions, and Ponco Waliko principles. While the forms of alternative dispute resolution is to use models Judge Partikulir, mediation lines, and Settlement Conference. The mechanism is made through rembugan process, the use of a mediator, the institutionalization of dispute resolution, and the execution of the verdict.Keywords: Pancasila, Local Wisdom, Dispute Resolution System